Pengaruh Kinerja Kerja Karyawan: Peran Work-Family Conflict, Motivasi Intrinsik, Motivasi Ekstrinsik pada PT Mjoint Yogyakarta - Irawan Arya Putra; Ignatius Soni Kurniawan; Nala Tri Kusuma (Trending: Jurnal Manajemen dan Ekonomi, 2024)
The purpose of this study was to determine the significance of the influence of work-family conflict, intrinsic motivation, and extrinsic motivation on the work performance of employees of PT MJOINT Yogyakarta. This study uses quantitative research methods and primary data in this study were taken using a questionnaire obtained by census on 68 respondents. Data analysis includes classical assumption tests and multiple linear regression analysis. The tests on classical assumption tests include normality tests, muticolonierity tests, and heteroscedasticity tests while multiple regression tests include t tests. This study shows that there is no influence from work-family conflict variables on employee work performance. There is a significant positive effect of instrinsic motivation variables on employee work performance. There is confirmation of a significant positive effect of extrinsic motivation variables on employee performance. Strengthening motivation is an implication to improve employee performance.